Origin of Groundwater Arsenic in a Rural Pleistocene Aquifer in Bangladesh Depressurized by Distal Municipal Pumping - Mozumder, M. R. H.; Michael, H. A.; Mihajlov, I.; Khan, M. R.; Knappett, P. S. K.; Bostick, B. C.; Mailloux, B. J.; Ahmed, K. M.; Choudhury, I.; Koffman, T.; Ellis, T.; Whaley‐Martin, K.; et al. (Water Resources Research, 2020)
Across South Asia, millions of villagers have reduced their exposure to high‐arsenic (As) groundwater by switching to low‐As wells. Isotopic tracers and flow modeling are used in this study to understand the groundwater flow system of a semi‐confined aquifer of Pleistocene (>10 kyr) age in Bangladesh that is generally low in As but has been perturbed by massive pumping at a distance of about 25 km for the municipal water supply of Dhaka. A 10‐ to 15‐m‐thick clay aquitard caps much of the intermediate aquifer (>40‐ to 90‐m depth) in the 3‐km2 study area, with some interruptions by younger channel sand deposits indicative of river scouring. Hydraulic heads in the intermediate aquifer below the clay‐capped areas are 1–2 m lower than in the high‐As shallow aquifer above the clay layer. In contrast, similar heads in the shallow and intermediate aquifer are observed where the clay layer is missing. The head distribution suggests a pattern of downward flow through interruptions in the aquitard and lateral advection from the sandy areas to the confined portion of the aquifer. The interpreted flow system is consistent with 3H‐3He ages, stable isotope data, and groundwater flow modeling. Lateral flow could explain an association of elevated As with high methane concentrations within layers of gray sand below certain clay‐capped portions of the Pleistocene aquifer. An influx of dissolved organic carbon from the clay layer itself leading to a reduction of initially orange sands has also likely contributed to the rise of As.
Keywords: Arsenic; Dhaka Bangladesh; groundwater pumping; modeling

The relation of geogenic contaminants to groundwater age, aquifer hydrologic position, water type, and redox conditions in Atlantic and Gulf Coastal Plain aquifers, eastern and south-central USA - Degnan, James R.; Lindsey, Bruce D.; Levitt, Joseph P.; Szabo, Zoltan (Science of The Total Environment, 2020)
Groundwater age distributions developed from carbon-14 (14C), tritium (3H), and helium-4 (4He) concentrations, along with aquifer hydrologic position, water type, and redox conditions, were compared to geogenic contaminants of concern (GCOC) from 252 public-supply wells in six Atlantic and Gulf Coastal Plain unconsolidated-sediment aquifers. Concentrations of one or more GCOCs in 168 (67%) wells exceeded MCLs (maximum contaminant levels), SMCLs (secondary MCLs), or HBSLs (health-based screening levels). Human-health benchmark thresholds (MCLs or HBSLs) were exceeded in 31 (12%) wells, and included 0.8% for fluoride (F), 2.4% for arsenic (As), 4% for lead-210 (210Pb), and 6.7% for polonium-210 (210Po). Values of pH increase with age and were outside the SMCL in 31% of wells (23% < 6.5 and 7.5% > 8.5, SMCL). Among GCOCs with concentrations that increased significantly with groundwater age, the frequency of sentry threshold exceedances (i.e., one-half of MCL, SMCL, or HBSL) included 40% for dissolved solids (DS), 12% for chloride (Cl), 3.6% for F, 4.4% for As, and 9.5% for 210Po. Iron (Fe) concentrations did not correlate with groundwater age, but exceeded sentry thresholds in 29% of wells. Groundwater age, water types, redox, pH, and GCOCs varied because of unique hydrogeologic features of the aquifers (recharge locations and geometry). As expected, primarily confined aquifers had young, oxic, low to near-neutral pH water near the outcrop (recharge area), and older, reduced, high pH water deeper and farther along flow paths. However, unique aquifer hydrogeologic conditions, such as multiple-recharge zones produced anomalous patterns of young and old groundwater at varying depths and locations along flow paths. Evidence for this variability is seen in disequilibrium patterns in the progression of the chemical evolution of groundwater with hydrologic position. When hydrogeologic differences are considered, groundwater age combined with hydrologic-position data, can provide a strong basis for inferring potential occurrence of GCOCs.
Keywords: Arsenic; Fluoride; Iron; Lead-210; pH; Polonium-210

The Impact of Aquifer Flushing on Groundwater Arsenic Across a 35‐km Transect Perpendicular to the Upper Brahmaputra River in Assam, India - Choudhury, R.; Nath, B.; Khan, M. R.; Mahanta, C.; Ellis, T.; Geen, A. (Water Resources Research, 2018)
Well testing in the floodplain of the Brahmaputra River in Golaghat and Jorhat districts of Assam, India, shows that groundwater arsenic (As) concentrations increase with distance from the river. To establish the origin of this pattern, an additional 900 wells <60‐m deep were tested for As and nine sites were drilled along a 35‐km transect perpendicular to the river. The field data show no relation between groundwater As concentrations ranging from <1 to 660 μg/L along the transect and (a) As concentrations of <1–5 mg/kg in cuttings of aquifer sand recovered while drilling or (b) the degree of reduction of iron oxides in these cuttings. The drilling indicates, however, a marked increase in the thickness of a clay layer capping the aquifer starting from <1–5 m near the river to over 60 m at the most distant site toward the base of the Naga foothills. Organic radiocarbon ages of 18–46 kyr obtained from all but one of 13 clay samples indicate pre‐Holocene deposition of the underlying sands across the entire transect. Radiocarbon ages of dissolved inorganic carbon of 0.2, 4.7, and 17.8 kyr were measured in groundwater from three monitoring wells installed to 30–60‐m depth at distances of 10, 20, and 40 km from the river, respectively. A conceptual groundwater flow model consistent with monitored heads and groundwater ages suggests that thick clay layers capping the aquifer further from the river inhibited flushing of the aquifer and, as a result, preserved higher As levels in groundwater.
Keywords: aquifer flushing; Arsenic; groundwater; South Asia